Environmental Factors Influencing Tobacco Usage among High School Children in Lucknow City: A Cross-sectional Study - Kankane, Nishita; Gupta, Vinay K; Mishra, Gaurav; Singh, S K; Malhotra, Shitanshu (Indian Journal of Community Health, 2023)
Background: Evidence proves that the majority of adult tobacco users begin using tobacco as children or teens. Teenagers are drawn to tobacco products for a variety of reasons. Public health planners are gravely concerned about the current rapid trade and tobacco use among teenagers in a developing nation like India. Objective: The present paper focuses on the prevalence of tobacco use among children in the eighth to tenth grades and the various environmental factors that contribute to tobacco use among children. Material and Methods: Following ethical clearance, six government schools in Lucknow were chosen for this cross-sectional study, and data was gathered using the Global Youth Tobacco Survey (GYTS) to examine the relationship between tobacco use in children and other independent influencing factors. Logistic regression analysis was used. Results: 21.7% of the children used tobacco in some or the other way. Supari with tobacco was the most popular tobacco product consumed by children (48.3%). Statistical analysis showed that family members consuming tobacco at home and adults sending their kid to get tobacco had a high connection with tobacco use among children. The direct relationship between children watching individuals consuming tobacco on television and their arousal of interest for the same was also seen. Similarly, the presence of tobacco vendors outside the school and easy availability of tobacco products to children significantly influenced the tobacco consumption habit. Conclusion: Tobacco users in families, adults sending children to buy tobacco, children’s arousal of interest on seeing people using tobacco on media, tobacco vendors outside the school, and the easy availability of tobacco products have all been proven to be environmental triggering factors for tobacco consumption amongst high school students.